Effective nonprofit management : context, concept, and competencies - Ahmed, Shamima, 1959- (Routledge, 2022)
"Underlining the relationship between the public and nonprofit sectors, Effective Nonprofit Management: Context, Concepts, and Competencies, 2nd Edition comprehensively explores of the practical art of forming, managing, and leading nonprofit organizations, contextualizing the changing socio-political conditions and expectations of key stakeholders in nonprofit organizations. Grounded in the practical experiences of real-life nonprofit managers, this thoroughly revised second edition explores contemporary issues that are becoming central to effective nonprofit management, including: an increasing emphasis on outcome assessment and accountability; innovative use of social media; big foundations' impacts on nonprofits and public policy making; tensions between federal, state, and local governments with nonprofits; and the importance of instilling a culture of ethics in the sector. A completely new chapter on nonprofit ethics and accountability has been added. Each chapter introduces the reader to relevant and current scholarship on the topic, utilizes the language of nonprofit practice, explores contemporary issues and examples, provides practical tips, includes text boxes with profiles of nonprofit organizations and best practices, and ends with a short and practical case study followed by discussion questions. Effective Nonprofit Management, Second Edition will be of interest to practitioners as well as graduate and upper division undergraduate students enrolled in nonprofit and public management courses"- Resumé vydavatel